Una mirada a Rabindranth - Lolas, Olga (Revista Chilena de Humanidades, 2015)
The author explores the relationship between T agore's life and his poeticcreativity through comments on texts especially selected by her. Her contentionis that Tagore is predominantly a lyrical poet, and that the use of the Bengalilanguage had a marked influence on his work, a considerable part of whichremains still unpublished. Prof. Lolas also assens that the true evolution ofTagore's work is to be found is his constant search for the Divine, and that hiswide acceptance within Western culture in no sense detracts from his Asiaticessence.